2018
DOI: 10.3126/jnhm.v30i0.27605
|View full text |Cite
|
Sign up to set email alerts
|

Status of crop raiding by Assamese monkeys (Macaca assamensis) along the Budhigandaki river, central Nepal

Abstract: Crop depredation study was done on Assamese monkeys (Macaca assamensis) in Budhigandaki river basin lying on Dhading and Gorkha districts of central Nepal. The field study was conducted from February 2015 to January 2016 spending 1804 hours to explore the ecology and feeding behavior of Assamese monkeys. The study mainly focused at Kallerivillage of Salang village development committee of Dhading district and Baseri, Majhitar and Siurenitar villages of Ghyalchok village development committee of Gorkha district… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The next study which was done along Budhigandaki river, that study found that maize was the highest raided crop, then it was followed by rice, lentil, peanut, soyabean, wheat, fruits, black pulses, potato etc. (Ghimire & Chalise, 2018). During the study in Langtang National Park (LNP) area, Chalise recorded that the crop depredation due to monkey species was highest in maize (43%) followed by potato (20%), millet (16%), wheat (13%), rice (7%) and buckwheat (1%) (Chalise, 2010).…”
Section: Type Of Raided Crop and Costmentioning
confidence: 99%
“…The next study which was done along Budhigandaki river, that study found that maize was the highest raided crop, then it was followed by rice, lentil, peanut, soyabean, wheat, fruits, black pulses, potato etc. (Ghimire & Chalise, 2018). During the study in Langtang National Park (LNP) area, Chalise recorded that the crop depredation due to monkey species was highest in maize (43%) followed by potato (20%), millet (16%), wheat (13%), rice (7%) and buckwheat (1%) (Chalise, 2010).…”
Section: Type Of Raided Crop and Costmentioning
confidence: 99%